Challenging material patterning: Fine lithography on coarse substrates. Issue 3 (29th October 2013) - Gilles, Sandra; Steppert, Ann‐Kathrin; Schaal, Patrick A.; Barth, Martin; Niewoehner, Ludwig; Simon, Ulrich
Summary Precise patterning of inorganic materials is important for many technological applications. Often lithography processes are required on challenging substrates with respect to topography, flexibility, and surface adhesion. Here we show the fabrication of artificial gunshot residues (GSR) on adhesive tape samples by means of dip‐pen lithography as an example for fine lithography on coarse substrates. We deposited lead‐, barium‐, and antimony‐containing inks on SEM adhesive tape by direct writing with a fine tip. Single as well as multiple element structures with dimensions in the range of 10–75 µm were fabricated. SCANNING 36:362–367, 2014. © 2013 Wiley Periodicals, Inc.